SENSORY MARKETING: AROMA DAN CITA RASA TERHADAP PEMBENTUKAN PERSEPSI KONSUMEN (STUDI KASUS: GERAI ROTI O DI STASIUN KRL COMMUTER LINE JAKARTA SELATAN) - Rania Rahmadhanimara; Titik Purwinarti; Ni Made Widhi S (EPIGRAM (e-journal), 2022)
This research aims to analyse the effect of sensory marketing through aroma and flavour toward the forming of consumer’s perception in Roti O’s Store in KRL commuter line Station at South Jakarta. This research is using quantitative method with 100 respondents as a sample. Slovin formula is used for sample drawing. This research passed the classic assumption test, in which the data is proved to have a normal distribution 0,200 > 0,050. The regression model Y = 1.835 + 1.938X1 – 0,621X2 + e shows the model is feasible to use. Based on partial regression analysis, aroma as an independent variable contributed to affect the consumer perception for 4,20%. Meanwhile flavour as an independent variable contributed to affect the consumer perception for 4,00%. Aroma and flavour simultaneously affecting the forming of consumer perception for 8,4%. The other 91,6% is being affected by other variables that are not being included in this research. The result shows that aroma does affect the forming of consumer perception and flavour doesn’t affect the forming of consumer perception. This research shows that aroma could be used for marketing strategy to build an impulse on consumer’s olfactory.